PENGARUH KINERJA PENGUNGKAPAN ESG TERHADAP KINERJA KEUANGAN DENGAN KEPATUHAN SYARIAH SEBAGAI VARIABEL MODERASI - Rahmansyah, Muhammad Faiz; Mutmainah, Siti (Diponegoro Journal of Accounting, 2024)
The purpose of this study is to examine how corporate financial performance is affected by environmental, social, and governance (ESG) disclosure performance, with a moderating variable from sharia compliance. In this study, financial performance is utilized as the dependent variable and is measured using Tobin’s Q. ESG disclosure performance is employed as the independent variable, proxied by the ESG score published on Bloomberg. This study also involves a moderating variable, which is shariah compliance measured by a dummy variable based on Indeks Saham Syariah Indonesia.Non-financial companies listed on the Indonesia Stock Exchange between 2019 and 2022 are the population that this study concentrates on. The sampling method utilized is purposive sampling, with a total of 58 companies chosen as samples for an observation period of 4 years. Data analysis is done using the Eviews 13 software comprised of descriptive statistical analysis, classic assumption test, panel data regression analysis, and moderated regression analysis (MRA).This study shows that environmental, social, and governance (ESG) disclosure performance impacted the company’s financial performance positively. While conducting the moderating test using MRA, it was discovered that shariah compliance has no moderating effect on the relationship between environmental, social, and governance (ESG) disclosure performance and the company’s financial performance.